Sains Dan Teknologi Dalam Ketamadunan Islam: Analisa Epistemologi Dan Metedologi - Elsa Maulidyah Syafira; Dina Firnanda Sari; Faesiyatul Lailiyah; Nurul Andiana; Alfina Wildatul Fitriyah (Lembaga Pengembangan Kinerja Dosen, 2024)
Science and technology have grown in tandem with the development pattern of human civilization in this universe. History of human civilization requires effort of manifestation of values in the scope of their own perspective. The statement above can be proved by the strong backup with meaning of scienceand technology itself, it is values and includes the cultural worldview formed by human itself. Science and technology have evolved in an orderly manner on the based on scientific research objectives. Innovation and creation of science and technology is influenced by the epistemology and methodology. Object of study in the disciplines of science and technology are also divided into different categories and also create its own subknowledge. This paper discusses aspects of the history of science and technology and also aspects of epistemology and methodology of science and technology in Islamic civilization.